Polymerization Shrinkage and Degree of Conversion of New Zirconia-Reinforced Rice Husk Nanohybrid Composite - Lin, Galvin Sim Siang (Eur J Dent, 2020)
Objectives  This study aimed to compare the polymerization shrinkage and degree of conversion of new zirconia-reinforced rice husk nanohybrid composite with commercialized microhybrid and nanofilled composites. Materials and Methods  Overall, 180 samples were used for polymerization shrinkage (buoyancy and optical methods) and degree of conversion tests in which they were divided into Group 1, nanofilled composite (Filtek-Z350- XT; 3M ESPE, St Paul, MN 55144-1000, USA), Group 2, microhybrid composite (Zmack-Comp), and Group 3, nanohybrid composite (Zr-Hybrid). Polymerization shrinkage test was performed using buoyancy and optical methods. For buoyancy method, samples were weighed in air and water to calculate the shrinkage value, whereas, for optical method, images of nonpolymerized samples were captured under a digital microscope and recaptured again after light-cured to calculate the percentage of shrinkage. Degree of conversion was tested using Fourier-transform infrared spectroscopy spectrometer. Statistical Analysis  Data were analyzed using one-way analysis of variance complemented by post hoc Dunnett’s T3 test for polymerization shrinkage and Tukey’s honestly significant difference test for degree of conversion. Level of significance was set at p < 0.05. Results  Group 3 demonstrated similar polymerization shrinkage with Group 1, but lower shrinkage ( p < 0.05) than Group 2 based on buoyancy method. However, optical method ( p < 0.05) showed that Group 3 had the lowest shrinkage, followed by Group 1 and lastly Group 2. Besides, Group 3 showed a significantly higher degree of conversion ( p < 0.05) than Group 1 and comparable conversion value with Group 2. Conclusions  Zirconia-reinforced rice husk nanohybrid composite showed excellent shrinkage and conversion values, hence can be considered as an alternative to commercially available composite resins.